'A Sinful Passion': Mario Vargas Llosa's Readings of Borges from 1964 to 2014. Issue 3 (16th March 2022) - Rossoni, Stefano
ABSTRACT: This article examines Vargas Llosa's fifty-year-long conflicted fascination for Jorge Luis Borges. The young and leftist Vargas Llosa disregarded Borges as the embodiment of a disengaged intellectual, while the mature Vargas Llosa celebrates him as the emblem of cosmopolitanism that should inspire globalized societies today. Focusing on different stages of Vargas Llosa's intellectual biography, I examine how his interpretations of Borges are informed by readings of Jean-Paul Sartre, Gabriel García Márquez and Miguel de Cervantes. Considering the intersections of political engagement and literary theories, I study how Vargas Llosa incorporates Borges' intellectualism into his fiction and imbues it with eroticism.